ANALYSIS OF SOURCES RELATED TO THE ADMINISTRATION OF MEDIEVAL CENTRAL ASIA - Zinatullaev Ziyodilla Izzatilla ugli (Web of Journals Publishing, 2025)
The article presents a source analysis of the history, style, content, manuscripts, translations, and modern editions of primary sources that provide valuable information about the history, culture, religion, rulers, social and economic situation, governance system, monetary and financial policy, tax collection, and other issues of the Samanids, Ghaznavids, Karakhanids, Seljuks, and Khwarazmshahs that ruled Central Asia in the 9th-12th centuries.
Keywords: Maimurg, Khurasan, Rome, Istanbul, Tehran and St. Petersburg, Tahirids, Saffaris, Samanids, Ghaznavids, Seljuks, Karakhanids.